2019
DOI: 10.1002/gcc.22808
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic recurrent ACIN1NUTM1 fusions in non‐KMT2A‐rearranged infant acute lymphoblastic leukemia

Abstract: Infant acute lymphoblastic leukemias (ALL) are rare hematological malignancies occurring in children younger than 1 year of age, most frequently associated with KMT2A rearrangements (KMT2A‐r). The smaller subset without KMT2A‐r, which represents 20% of infant ALL cases, is poorly characterized. Here we report two cases of chemotherapy‐sensitive non‐KMT2A‐r infant ALL. Transcriptome analyses revealed identical ACIN1‐NUTM1 gene fusions in both cases, derived from cryptic chromosomal rearrangements undetected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 24 publications
(53 reference statements)
1
10
0
Order By: Relevance
“…Based on the above method, 5 genes, including STX16, CLASRP, ATIC, ACIN1 and SEMA4B, were identified to be relevant to poor prognosis of ccRCC patients. It has been reported that high serum levels of STX16 was associated with esophageal squamous cell carcinoma (24), CLASRP was associated with head and neck cancers (25), ATIC promoted the development of hepatocellular carcinoma (26) and hypermethylated ACIN1 was observed in lung adenocarcinoma and acute lymphoblastic leukemia (27,28). This correlates with the observations from long-term follow-up studies that cancer patients carrying these up-regulated genes exhibited poor prognosis (Figure 3C).…”
Section: Discussionsupporting
confidence: 85%
“…Based on the above method, 5 genes, including STX16, CLASRP, ATIC, ACIN1 and SEMA4B, were identified to be relevant to poor prognosis of ccRCC patients. It has been reported that high serum levels of STX16 was associated with esophageal squamous cell carcinoma (24), CLASRP was associated with head and neck cancers (25), ATIC promoted the development of hepatocellular carcinoma (26) and hypermethylated ACIN1 was observed in lung adenocarcinoma and acute lymphoblastic leukemia (27,28). This correlates with the observations from long-term follow-up studies that cancer patients carrying these up-regulated genes exhibited poor prognosis (Figure 3C).…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, BRD9, while not categorized as a BET protein, contains a single bromodomain and binds the lysine residues of acetylated histones. ACIN1‐NUTM1 fusions have now also been reported on several more occasions in infant and pediatric ALLs . Other NUTM1 fusion partners reported in ALL are IKZF1 , ZNF618 , AFF1 , SLC12A6 , CUX1 , and BPTF …”
Section: Nutm1‐associated Allmentioning
confidence: 89%
“…ACIN1-NUTM1 fusions have now also been reported on several more occasions in infant and pediatric ALLs. 72,[76][77][78][79] Other NUTM1 fusion partners reported in ALL are IKZF1, 76 With a single exception, all of these NUTM1 fusion partners are predicted to associate directly with DNA and/or participate in chromatin remodeling. The exception, solute carrier family 12 member 6 (SLC12A6), also known as K-Cl cotransporter C (KCC3), is a member of the K-Cl cotransporter family.…”
Section: Max Dimerization Protein (Mad)-nutm1 Tumorsmentioning
confidence: 99%
“…Recently, NUTM1 is becoming less specific for NC, and many novel fusion partner genes were identified in sarcoma and hematologic malignancy. 39,[41][42][43][44][45][46] Nineteen cases of NUTM1-associated sarcoma were summarized in the Table 5 45 The prognosis of NUTM1-associated sarcoma is generally poor, except one ZNF532, one MXD1, two MGA, and one CIC fusion partner gene cases. In IHC, most NC cells showed positivity for squamous cell markers, p63 and p40, and about half of cases showed immunoreactivity for CD34.…”
Section: Discussionmentioning
confidence: 99%